Exploring Consumers’ Technology Acceptance Behavior Regarding Indoor Smart Farm Restaurant Systems: Focusing on the Value-Based Adoption Model and Value–Attitude–Behavior Hierarchy - Kyuhyeon Joo; Jinsoo Hwang (Systems)
This study examines consumers’ technology acceptance behavior regarding indoor smart farm restaurant systems focusing on the value-based adoption model and value–attitude–behavior hierarchy. More specifically, the study explores the effects of the benefits (i.e., perceived naturalness, psychological benefits, healthy well-being, and enjoyment) and sacrifices (i.e., perceived fee, perceived risk, and food technophobia) on perceived value. This study also probes the influence of perceived value on attitude and intentions to use and the relationship between attitude and intentions to use. The data were collected from 360 respondents in South Korea. The data analysis results indicate that all the benefit factors positively affect perceived value, whereas only food technophobia negatively affects perceived value among the sacrifice factors. Lastly, perceived value aids in the formation of attitude, while perceived value and attitude have a positive influence on intentions to use.